2015
DOI: 10.3758/s13414-015-0851-3
|View full text |Cite
|
Sign up to set email alerts
|

Irrelevant reward and selection histories have different influences on task-relevant attentional selection

Abstract: Task-relevant and physically salient features influence visual selective attention. In the present study, we investigated the influence of task-irrelevant and physically nonsalient reward-associated features on visual selective attention. Two hypotheses were tested: One predicts that the effects of target-defining task-relevant and task-irrelevant features interact to modulate visual selection; the other predicts that visual selection is determined by the independent combination of relevant and irrelevant feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 37 publications
7
25
0
Order By: Relevance
“…Interestingly, similar findings have been documented in studies using reward-associated stimuli, suggesting that value-driven attentional biases take effect rapidly and automatically, like exogenous biases, while goal-driven attentional control appears to require additional time to relate the available sensory input with any existing strategic goals in order to elicit an appropriate response (MacLean & Giesbrecht, 2015a; Mulckhuyse & Theeuwes, 2010; Theeuwes & Belopolsky, 2012). For example, in a recent visual search study by Failing, Nissens, Pearson, Le Pelley and Theeuwes (2015), it was shown that the fastest saccades went to a colour distractor that signalled the possibility of receiving a reward while slower saccades typically went to the coloured target.…”
supporting
confidence: 60%
“…Interestingly, similar findings have been documented in studies using reward-associated stimuli, suggesting that value-driven attentional biases take effect rapidly and automatically, like exogenous biases, while goal-driven attentional control appears to require additional time to relate the available sensory input with any existing strategic goals in order to elicit an appropriate response (MacLean & Giesbrecht, 2015a; Mulckhuyse & Theeuwes, 2010; Theeuwes & Belopolsky, 2012). For example, in a recent visual search study by Failing, Nissens, Pearson, Le Pelley and Theeuwes (2015), it was shown that the fastest saccades went to a colour distractor that signalled the possibility of receiving a reward while slower saccades typically went to the coloured target.…”
supporting
confidence: 60%
“…One possibility is that top–down processes, such as volitional control or stimulus‐associated reward (e.g., Bucker & Theeuwes, ; Lupiåñez, Weaver, Tipper, Madrid, & Castillo, ; Tipper & Kingstone, ), might explain our findings. For example, associating a stimulus with a previously learned reward captures attention (Anderson, Laurent, & Yantis, ), and it improves target discrimination (Maclean & Giesbrecht, ). Importantly, in our study, we found that higher compared to lower ranked interaction partners only had a differential effect on interpersonal spatial orienting, when being task relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Although previously reward‐associated stimuli are capable of capturing attention even when inconspicuous and task irrelevant, and even when the target competing with the previously reward‐associated stimulus also has high attentional priority (by virtue of its affective valence), goal‐directed attentional control has been shown to modulate the effect of learned value on attention. Attentional capture by previously reward‐associated stimuli is stronger when such stimuli also possess a task‐relevant feature . Attentional biases for reward‐associated stimuli are also stronger when they can appear as a rewarded target, and expectations concerning the target location can modulate the attentional processing of reward‐associated stimuli .…”
Section: Representation and Neural Basismentioning
confidence: 99%
“…117,120 Attentional biases for reward-associated stimuli are also stronger when they can appear as a rewarded target, 121 and expectations concerning the target location can modulate the attentional processing of rewardassociated stimuli. 117,120,122 Mindfulness training, which requires intense attentional focus, has been shown to reduce the impact of reward-associated distractors on performance. 123 It is tempting to hypothesize the existence of a common priority map to which value-driven, goal-directed, and stimulusdriven influences contribute to the competition for selection.…”
Section: Representation and Neural Basismentioning
confidence: 99%